Strategi Pemasaran 4P pada Usaha Kerajinan Tangan Accessoris di Bengkayang - Rosaria, Meitigsa Andri; Hapsari, Veneranda Rini (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the marketing strategy used by the handicraft business Caa Handmade to attract consumers to buy in the Shanti Bhuana campus and dormitory environment. This research was conducted at the Shanti Bhuana campus and dormitory, Jl. Bukit Karmel No.1 Sebopet, Bengkayang. The research was conducted using qualitative methods through data collection techniques, namely observation, interviews and documentation. The results of the research conducted show that to attract consumers' interest in CHM products, an appropriate marketing strategy is needed. The marketing strategy used in this research is Product, Price, Place and Promotion. Every part of the marketing strategy used by the CHM business to attract consumer interest has an important role and is interrelated with one another so that this will help business continuity